Analisis Sistem Informasi Akuntansi Penggajian Dan Pengupahan Dalam Upaya Pengendalian Internal Pada PT. Srijasa Brika Perkasa Palembang - Astuti, Dewi; Helmi, Sulaiman; Sartika, Dewi; Gustini, Emilia (CV. ITTC INDONESIA, 2024)
This research aims to determine the internal control of PT. Srijasa Brika Perkasa as well as payroll and business wage accounting data systems. Descriptive analysis was used in this research. Three approaches were used to obtain data: documentation, observation, and interviews. The analysis findings show that, although there are several weaknesses, internal control has generally been implemented well. One of them is the finance department which still handles many tasks, such as paying salaries and wages to employees, making payroll, and recording attendance. Apart from that, employee attendance list data is still modified manually, so that the list only contains attendance times. In addition, the lack of supervision of staff attendance records shows the company's vulnerability as a result of inadequate internal control systems in payments.